Polymers for lightwave and integrated optics technology and applications - Hornak, Lawrence A. (Optical engineering (Marcel Dekker, Inc.), 1992)
This unique, single-source reference offers the entire field of polymer integrated topics, including passive polymer materials and their applications, and second- and third-order nonlinear materials.